Nasolabial Ulcerated Placard Revealing a Primary Cutaneous Aggressive Epidermotropic CD8+ T-cell Lymphoma - J. B. Ntihebuwayo; F. Hali; A. Kerouach; H. Rachadi; S. Chiheb; F. Marnissi (Case Reports in Dermatological Medicine)
Primary cutaneous aggressive epidermotropic CD8+ T-cell lymphoma is a rare entity representing less than 1% of cutaneous lymphomas. It has an aggressive clinical manifestation with a poor prognosis. It is characterized by cytotoxic and epidermotropic CD8+ proliferation. It also expresses the TIA-1 marker. We report a new case for its display and aggressive character, diagnostic difficulty, and good therapeutic response to chemotherapy. This is a 62-year-old female patient admitted to the hospital for a nasolabial ulcerated placard evolving for two years. Clinical examination revealed submandibular lymph nodes. The specimen analysis associated with anatomoclinical manifestation was concluded for a primary cutaneous aggressive epidermotropic CD8+ T-cell lymphoma. Tumor extent assessment did not show any secondary localization. The blood tests and serology were unremarkable. The patient had benefited from a CHOEP-type multidrug therapy protocol with complete healing of the lesion after three courses of chemotherapy.